The Effect of Service Communication Process and Customer Service Officer Complaint Handling on Satisfaction and Loyalty (Literature Review Marketing Management) - Agustin Hermawati (Dinasti Publisher, 2022)
Article Literature Review of the Effect of Service Communication Process and handling complaints of customer service officers on customer satisfaction and loyalty of PT Bank Rakyat Indonesia (Persero) is a scientific article aimed at building research hypotheses of influence between variables that will be used in further research, within the scope of marketing management science. This Literature Review Article Writing Method is the Research Library Method, sourced from online media such as Google Scholar, Mendeley, and other academic online media. The results of the article literature article are 1) the service communication process affects satisfaction; 2) Handling of Customer Service Officer complaints affects satisfaction; 3) the Service communication process affects customer loyalty; 4) Handling of Customer Service Officer complaints affects customer loyalty, and 5) satisfaction affects customer loyalty. In addition to these two exogenous variables that affect the endogenous variable of customer satisfaction and loyalty, there are still many other factors, including brand reputation variables, strategic locations, commitment, and trust.